Hydraulic dilation with a shape-measuring balloon in idiopathic achalasia: a feasibility study - Kappelle, Wouter F. W.; Bogte, Auke; Siersema, Peter D. (Endoscopy, 2015)
Background and aim: Pneumatic dilation is a commonly used treatment in achalasia. Recent studies have shown that esophageal distensibility measurements can be used to assess the effect of dilation and possibly the risk of perforation. A new hydraulic dilation balloon allows visualization of the shape of the balloon in vivo and measurement of distensibility during dilation. We aimed to evaluate the technical feasibility of a 30-mm shape-measuring hydraulic dilation balloon for the treatment of achalasia.Methods: Consecutive patients with newly diagnosed achalasia were dilated using a 30-mm shape-measuring hydraulic dilation balloon. Patients were contacted 1 week, 1 month, and 3 months after dilation. Technical success, clinical success, and major complications were evaluated. Results: Technical success was achieved in all of the 10 patients included. Median esophagogastric junction distensibility (mm2/mmHg) increased from 1.1 (IQR 0.6 – 1.3) before dilation therapy to 7.0 (IQR 5.5 – 17.8) afterwards (P = 0.005). No major complications were seen. Three patients (30 %) reported recurrent dysphagia.Conclusion: Hydraulic dilation with a shape-measuring balloon in achalasia patients is feasible. In vivo esophageal distensibility measurements may allow for an individualized, patient-specific dilation regimen.The Netherlands National Trial Register: NTR4371